2014
DOI: 10.1371/journal.pone.0097726
|View full text |Cite
|
Sign up to set email alerts
|

Declining Incidence of Hepatitis C Virus Infection among People Who Inject Drugs in a Canadian Setting, 1996-2012

Abstract: BackgroundPeople who inject drugs (PWID) are at high risk of hepatitis C virus (HCV) infection. Trends in HCV incidence and associated risk factors among PWID recruited between 1996 and 2012 in Vancouver, Canada were evaluated.MethodsData were derived from a long-term cohort of PWID in Vancouver. Trends in HCV incidence were evaluated. Factors associated with time to HCV infection were assessed using Cox proportional hazards regression.ResultsAmong 2,589, 82% (n = 2,121) were HCV antibody-positive at enrollmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
1
43
1
Order By: Relevance
“…These results were consistent with the findings reported by Urbanek et al (2010) based on proportional scores and Crivelli et al (2012) based on residualized scores. A small difference was also found on proportional scores relating to the orienting network, a result that has also been recently reported by Vazquez-Marrufo et al (2014) based on proportional scores.…”
Section: Discussionsupporting
confidence: 84%
“…These results were consistent with the findings reported by Urbanek et al (2010) based on proportional scores and Crivelli et al (2012) based on residualized scores. A small difference was also found on proportional scores relating to the orienting network, a result that has also been recently reported by Vazquez-Marrufo et al (2014) based on proportional scores.…”
Section: Discussionsupporting
confidence: 84%
“…1-3 HCV transmission is driven by a high incidence of infection among PWID, particularly among young PWID. [4][5][6] The majority of those infected fail to clear the virus and also fail to develop protective immunity. [7][8][9][10] As such, PWID are likely to be exposed to multiple HCV infections as a result of ongoing high-risk behaviours and might commonly harbour mixed HCV infections (that is, infection with two or more distinct viruses).…”
Section: Introductionmentioning
confidence: 99%
“…The lower proportion with clustering in this study compared to previous studies might be due to several different reasons. First, there was a lower prevalence of HCV among at-risk PWID in this study, partly related to a decreased HCV incidence observed among PWID in Vancouver over the past two decades (Grebely et al, 2014). Further, participants were sampled more broadly throughout the Greater Vancouver region compared to previous studies of long-term PWID in the Vancouver Downtown Eastside neighbourhood (a restricted geographical area known for having a highly concentrated population of PWID).…”
Section: Discussionmentioning
confidence: 77%
“…However, previous data have demonstrated that methamphetamine injection was independently associated with acquisition of HCV infection (Grebely et al, 2014; Hadland et al, 2014; Miller et al, 2009). Methamphetamine use in any form among street-involved youth in Vancouver has increased from 2.5% in 1999 to 10.5% in 2011, consistent with global trends (Lianping et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation